2003
DOI: 10.1053/jvet.2003.50000
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Two Modifications of Unilateral Arytenoid Lateralization on Rima Glottidis Area in Dogs

Abstract: CTAL is as effective as CAL in providing an increased rima glottidis for the treatment of bilateral laryngeal paralysis in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 9 publications
1
49
0
Order By: Relevance
“…Besides, the glottic index was adopted as it represents a constant ratio between two actual measurements; if the glottic area is used instead, differences in pixel measurement may arise from different distances between the operator and glottis. As an alternative, a dedicated ruler adjacent to the laryngeal opening would have been valuable in providing a scale [40,41]. In the present study, statistical evaluation of the measurements taken by two different operators demonstrated that results were repeatable.…”
Section: Discussionmentioning
confidence: 70%
“…Besides, the glottic index was adopted as it represents a constant ratio between two actual measurements; if the glottic area is used instead, differences in pixel measurement may arise from different distances between the operator and glottis. As an alternative, a dedicated ruler adjacent to the laryngeal opening would have been valuable in providing a scale [40,41]. In the present study, statistical evaluation of the measurements taken by two different operators demonstrated that results were repeatable.…”
Section: Discussionmentioning
confidence: 70%
“…Good clinical results were reported with an increase in rima glottidis area of approximately 250% (Demetriou and Kirby 2003) and 140% (thyroarytenoid) and 207% (cricoarytenoid) (Griffiths et. al.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…polypropylene) on a tapercut needle is recommended for fixing the arytenoid. Depending on the size of the dog, USP 2/0 (< 40 kg) or USP 0 (> 40 kg) is used (Demetriou & Kirby 2003). The suture is anchored dorsally on the caudal border of the cricoid cartilage, taking care not to penetrate the laryngeal lumen.…”
Section: Surgical Treatment By Cricoarytenoid Cartilage Lateralisationmentioning
confidence: 99%
“…It should be kept in mind that dogs carry a lifelong risk for the development of respiratory tract complications postoperatively (MacPhail & Monnet 2001). Aspiration pneumonia is the most frequently noted complication, occurring in about 8% -24% of dogs postoperatively (Demetriou & Kirby 2003;Hammel et al 2006;MacPhail & Monnet 2001;Snelling & Edwards 2003;White 1989). Low-tension techniques are believed to decrease the incidence of postoperative aspiration pneumonia (Bureau & Monnet 2002).…”
Section: Surgical Treatment By Cricoarytenoid Cartilage Lateralisationmentioning
confidence: 99%